Fallot and Its Variants: From Diagnosis to Pulmonary Valve Replacement - Rüffer, André; Bertram, Harald (The Thoracic and Cardiovascular Surgeon, 2025)
In this article, we summarize the most important issues and recommendations on the anatomy and physiology of tetralogy-like lesions, diagnosis prior to medical, interventional, or surgical intervention, timing and types of interventions, management of high-risk patients, and the need for future interventions in a subset of patients. The long versions of the original guidelines are reprinted in the supplement, providing a more comprehensive overview and enabling a more detailed approach to tetralogy and its variants.
Keywords: congenital heart disease; Tetralogy of Fallot; Double outlet right ventricle; Pulmonary atresia with ventricular septal defect; Pulmonary valve replacement